Postoperative complications following percutaneous endoscopic gastrostomy are common in children. (8th May 2017) - Hansen, E; Qvist, N; Rasmussen, L; Ellebæk, MB
Abstract: Aim: Inserting a feeding tube using percutaneous endoscopic gastrostomy may be necessary to ensure that children with eating problems receive sufficient enteral nutrition. The aim of this study was to investigate the perioperative and postoperative complications of percutaneous endoscopic gastrostomy when the pull‐through method was the standard procedure. Methods: This was a retrospective review of 229 children (50.7% male) who underwent a gastrostomy procedure at Odense University Hospital, Denmark, from January 1, 2000 to December 31, 2012. The median age of the children was 1.6 years (range: 0–14.9), and the follow‐up period was 36 months. Complications were graded according to the Clavien‐Dindo classification. Results: A total of 167 postoperative complications occurred in 118 of the 229 patients (51.5%). Of these, 89 were grade 1 complications, 49 were grade 2 complications, and 29 were grade 3b complications. No gastrostomy‐related deaths were observed, and no single preoperative risk factor was identified. Perioperative complications were experienced by 2.6% of the patients. Conclusion: Gastrostomy feeding tube placement was associated with a high rate of postoperative complications of various grades when the pull‐through method was the standard procedure. A consensus on how to report and grade complications arising from this procedure is warranted.